2020
DOI: 10.1017/jpa.2020.25
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic analysis of Anisian (Middle Triassic) ptychitid ammonoids from Nevada, USA

Abstract: Ptychites is among the most widely distributed ammonoid genera of the Triassic and is namesake of a family and superfamily. However, representatives of the genus mostly show low-level phenotypic disparity. Furthermore, a large number of taxa are based on only a few poorly preserved specimens, creating challenges to determine ptychitid taxonomy. Consequently, a novel approach is needed to improve ptychitid diversity studies. Here, we investigate Ptychites spp. from the middle and late Anisian of Nevada. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…The process of lengthening and shortening of the trajectories (i.e., related to changes in rate and timing of the development) account for the ontogenetic differentiation of the species in focus. This contrasts a previous traditional morphometric analysis by Bischof & Lehmann (2020) of ptychitids, which revealed that the spherocone-cadicone morphospace is much more distinct. The highly ontogenetically differentiated genus Ptychites directly differed through characteristic ontogenetic trajectories.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The process of lengthening and shortening of the trajectories (i.e., related to changes in rate and timing of the development) account for the ontogenetic differentiation of the species in focus. This contrasts a previous traditional morphometric analysis by Bischof & Lehmann (2020) of ptychitids, which revealed that the spherocone-cadicone morphospace is much more distinct. The highly ontogenetically differentiated genus Ptychites directly differed through characteristic ontogenetic trajectories.…”
Section: Discussioncontrasting
confidence: 99%
“…The results obtained here do justice to the general opinion that ontogenetic trajectories can be a powerful tool to describe (e.g., Korn & Klug, 2007) and discriminate ammonoid species (e.g., Rieber, 1962;Bischof & Lehmann, 2020): The newly introduced methods succeeded in statistically discriminating the ontogenetic pathways of the pre-defined ceratitid species. Based on this analysis, the high diversity of the Anisian ammonoid assemblages of Nevada appears not to be artificially inflated and the alpha taxonomy is regarded to be adequate.…”
Section: Anisian Ammonoid Diversitysupporting
confidence: 58%
See 3 more Smart Citations